Aerodynamic mechanisms in bio‐inspired micro air vehicles: a review in the light of novel compound layouts. Issue 1 (4th October 2019) - Chen, Long; Zhang, Yanlai; Zhou, Chao; Wu, Jianghao
Abstract : Modern designs of micro air vehicles (MAVs) are mostly inspired by nature's flyers, such as hummingbirds and flying insects, which results in the birth of bio‐inspired MAVs. The history and recent progress of the aerodynamic mechanisms in bio‐inspired MAVs are reviewed in this study, especially focused on those compound layouts using bio‐inspired unsteady aerodynamic mechanisms. Several successful bio‐mimicking MAVs and the unsteady high lift mechanisms in insect flight are briefly revisited. Four types of the compound layouts, i.e. the fixed/flapping‐wing MAV, the flapping rotary wing MAV, the multiple‐pair flapping‐wing MAV, and the cycloidal rotor MAV are introduced in terms of recent findings on their aerodynamic mechanisms. In the end, future interests in the field of MAVs are suggested. The authors' review can provide solid background knowledge for both future studies on the aerodynamic mechanisms in bio‐inspired MAVs and the practical design of a bio‐inspired MAV.